Beastly beasts - John Mclay (London; Orion Children's Books, 2016)
It's never too early to find out about brilliant beasts and mythical creatures with this brand new green Early Reader factbook. Early Readers are stepping stones from picture books to reading books, perfect for building confidence in new readers and reluctant readers. A green Early Reader is a first factbook. Did you know that and that people used to believe in fire-breathing dragons and that no one has ever seen the Loch Ness Monster up close? Learn fascinating facts about brilliant beasts and mythical creatures in this brand new non fiction Early Reader from John McLay, with full colour illustrations on every page
Keywords: Readers